The relationship between hot flashes and fatty acid binding protein 2 in postmenopausal women - Chen, Ting-Yu; Huang, Wan-Yu; Liu, Ko-Hung; Kor, Chew-Teng; Chao, Yi-Chun; Wu, Hung-Ming (PloS one, 2022)
Hot flashes, the most bothering symptom of menopause, are linked to a metabolic inflammation. Due to estrogen deficiency in menopause, dysbiosis is observed. The intestinal barrier affects the interaction of microbiota in healthy or unhealthy individuals. This study investigates the relationship between hot flashes and gut permeability in postmenopausal women. In this cross-sectional study, we divided 289 women, aged 40-65 years, into four groups based on their hot-flash severity: HF.sub.0 : never experienced hot flashes; HF.sub.m : mild hot flashes; HF.sub.M : moderate hot flashes; HF.sub.S : severe hot flashes. The measured variables included the clinical parameters; hot flashes experience; fasting plasma levels of zonulin, fatty acid binding protein 2 (FABP2), endotoxin, and cytokines/chemokines. We used multiple linear regression analysis to evaluate the relationship between hot flashes and the previously mentioned gut barrier proteins. The study was performed in a hospital medical center. The hot flashes had a positive tendency toward increased levels of circulating FABP2 (P-trend = 0.001), endotoxin (P-trend = 0.031), high-sensitivity C-reactive protein (hs-CRP) (P-trend = 0.033), tumor necrosis factor alpha (TNF-[alpha]) (P-trend = 0.017), and interferon-inducible protein-10 (IP10) (P-trend = 0.021). Spearman's correlation analysis revealed significant correlations of FABP2 with endotoxin, TNF-[alpha], monocyte chemoattractant protein-1, IP10, and hs-CRP in the 289 postmenopausal women included in this study. Linear regression analysis revealed that hot-flash severity had significant assoiciations with FABP2 (P-trend = 0.002), but not with zonulin. After adjusting for body mass index, age, and menopause duration, multivariate linear regression analysis revealed the differences between HFs (% difference (95% confidence interval), 22.36 (8.04, 38.59), P = 0.01) and HF.sub.0 groups in terms of FABP2 levels. This study shows that hot flashes are significantly associated with FABP2 levels in postmenopausal women. It suggests that severe hot flashes are linked to an increase in intestinal barrier permeability and low-grade systemic inflammation.